A New Brussels Consensus? Qatargate and the (Re)articulation of EU International Development Cooperation Governance - Murphy, Susan P.; McMahon, Cian (Taylor & Francis, 2025)
As the polycrisis of the current conjuncture interacts and unfolds across sites and scales, the core democratic institutions of the European Union experienced their own localised crises of confidence and legitimacy with the eruption of Qatargate, a bribery and corruption scandal involving cash transfers through fake non-governmental organisations (NGOs) to European Parliamentarians, in December 2022. In response, parliamentary debates called for reform of accountability and transparency mechanisms for EU NGOs and their collaborating non-EU NGO partners funded by and through the European Union (EU). But what are the implications and risks of such reforms? Is Qatargate a cause or a symptom of a shift towards enhanced EU/state control of NGOs? We examine the longer-term geo-historical context within which this crisis is embedded and undertake a critical policy analysis of EU policies and parliamentary deliberations on development cooperation and NGO accountability and transparency to address these questions. We find evidence of a distinct drift over time from universal to EU values and interests with a deepening role for the EU/state in controlling NGO relations and augmenting private sector involvement in development cooperation through de-risking mechanisms. We argue that an emerging Brussels Consensus problematises NGO collaboration with non-EU partners, legitimises EU/state-centred developmentalism, and risks the co-option of NGO capacities in the service of EU-state centred interests. Such shifts are consequential to processes of democratisation, governance, and human rights inside and outside the EU.
PUBLISHED
Keywords: International development; Governance; European Development Cooperation Policy; International Development; Development; Policy